Idea compassio fraterna w parenetycznej instrukcji Dhuody z Septymanii († ok. 843) - Chudzikowska-Wołoszyn, Małgorzata (Vox Patrum, 2019)
The present article is about an idea of compassio fraterna which was proclaim by Carolingian scientist Dhuoda from Septimania and was related to ability of brotherly compassion and co-suffering and it was given a birth to a such important thing as a Christian soul bond as well. The author is trying to bring closer the definition of brotherly love which Dhuoda considered on a biological and spiritual level and she defined a belonging to it moral values and flowing from them reciprocal obligations consequent as well. There are pictured a sources which were inspiration for Carolingian scientist who for her juvenile son created her own crystal concept of model-based Christian brotherhood. A base to analisys is a Liber manualis (Handbook) - the only composition written by marchioness Septimania.